Exploring Code Switching in Boy William’s YouTube Interview with Maudy Ayunda - Paramita Kristinadewi, Ni Made Ayu; Eka Pratiwi, Desak Putu (Humanis; Vol 28 No 1 (2024), 2024)
This study explores the phenomenon of code-switching in the YouTube video “Maudy Ayunda Sempat Merasa Insecure Saat Berada di Stanford” uploaded by Boy William. The analysis focuses on the types of code switching employed in the conversation between the interviewer (Boy William) and the interviewee (Maudy Ayunda). The data were collected from the announcers utterances by (1) downloading the video (2) watching the related video repeatedly (3) taking notes on the dialogue that contains code switching, and (4) classifying. The writer using descriptive qualitative method. The theoretical framework, drawing from Hoffman (1991) and Grosjean (1982), provides the types and the reasons of code switching. The results of the analysis showed four types of code switching with the most shown namely Establishing Continuity frequency 18 with 43,9 %, while the least is Inter-sentential Switches frequency 4 with 9,7%.